Management of in-situ surface collections at Great Zimbabwe World Heritage Site - Chamanga, Dean T. (Midlands State University, 2018)
The study sought to investigate the policies and protocols of managing in-situ surface collectionsat Great Zimbabwe WHS. The research employed a number of methodological approaches that included surveying, mapping, observations, interviews and review of documents such as site conservations reports and memorandums to understand and collect data for the management of in-situ surface collections at Great Zimbabwe which was essential in addressing the research objectives. The research objectives were to identify the policies and protocols and the role of managing in-situ surface collections. To identify the variability, density and distribution of surface collections and to assess the impact of fireguards to in-situ surface collections.The study confirms that indeed there are policies in the management of in-situ surface collections at the site and that there is a great deal of surface collections found in variability across the Great Zimbabwe landscape the include potsherds, glass beads and dagga structures which play a significant role in the reconstruction of past activities at Great Zimbabwe World Heritage Site. The study also indicated negative impact of fireguard clearance to in-situ surface collections. Consequently this study relatively suggests that these policies formally recognize the international, national and local interests in the preservation of in-situ surface collections. However NMMZ is failing to be assertive and to effective in implementing these policies in some cases of development at the site which has a detrimental effect in the management of insitu surface archaeological deposits.